"I will never forget him". A qualitative exploration of staff descriptions of helpful relationships in supportive housing. Issue 3 (23rd July 2020) - Lindvig, Gunnhild Ruud; Topor, Alain; Bøe, Tore Dag; Larsen, Inger Beate
Accessible Summary: What is known on the subject?: Recovery‐oriented studies show that the quality of the professional relationship plays an essential role in the recovery from mental illness. Within mental health care in general, previous studies show that helpful professional relationships are characterized by several reciprocal aspects, such as friendship resemblance and self‐disclosure. The literature is scarce on in‐depth explorations of professional relationships within the often long‐lasting and intimate help context of institutional supportive housing. Explorations of staff members' experiences are absent. The scientific rationale of this study was to expand the current knowledge about professional relationships in mental health care by exploring staff members' descriptions of helpful professional relationships in supportive housing institutions. What this paper adds to existing knowledge: The study shows that helpful relationships may involve staff experiences of reciprocity in terms of both a two‐way influence between staff and residents and a reciprocal gain from being part of the helpful relationships. A conceptualization of reciprocity that complements existing concepts is suggested and connected to a "good match" between staff and residents. What are the implications for practice?: When support and care are intended to be provided within a dyadic relationship, both parties' preferences should be considered when pairing service users and professionals. Practitioners should get involved in ways that open up for being influenced and inspired by the service user's characteristics, such as personality and attitude. Furthermore, they should dare to enjoy and make use of the company of the service user in ways that promote multifaceted reciprocity. Abstract: Introduction: In the aftermath of the deinstitutionalization in western countries, new community‐based mental health services have been established. An essential object of studies in this new institutional landscape has been helpful professional relationships, but we still lack knowledge about helpful relationships in community‐based institutional supportive housing. Aim: To explore how staff members describe their relationships with residents who have identified them as helpful. Methods: Qualitative interviews with nine staff members were analysed using thematic analysis. Results: "Reciprocity" was identified as the main theme, and two subthemes were developed: "Something influential about the resident" and "Value for the staff member." Discussion: The findings are discussed and related to existing conceptualizations of reciprocity in professional relationships, and an additional conceptualization is suggested. Implications for practice: To promote reciprocity, managers should consider both parties' personal preferences when matching professionals and service users. Further, professionals should get involved in ways that open up for being influenced and inspired by several of the service user's characteristics. They should allow themselves to enjoy the company of the service user in ways that promote multifaceted reciprocity.